Challenges Encountered by Police Officers in the Implementation of Republic Act 9165 in Barangay Bignay Valenzuela City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to evaluate the challenges encountered by police officers in theimplementation of Republic Act 9165 in Barangay Bignay, Valenzuela City, in terms ofcommunity support, police officers, and intelligence. The respondent of the study is theselected police officer in VCPS Sub-station 7 Bignay to answer the questions presented in thestudy of challenges encountered in the implementation of Republic Act 9165. The targetpopulation is thirty (30) police officers in Barangay Bignay, Valenzuela City. This study givesthe respondents and future researchers additional knowledge and information about thechallenges encountered by police officers in implementation of Republic Act 9165, whichhelps to provide solutions to the given challenges. Future researchers could also explore andresearch the challenges encountered by police officers in the implementation of Republic Act9165.
Keywords: Criminology